(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the mechanisms for improving students’ professional training on the basis of an individual approach in pedagogical education. The relevance of the topic is determined by the growing need to prepare future specialists who are able to demonstrate professional competence, independent thinking, adaptability, responsibility, and readiness for practical activity in a rapidly changing educational and social environment. The individual approach is considered as an important pedagogical principle that allows the educational process to be organized according to students’ abilities, interests, learning pace, motivation, professional orientation, and personal development needs. The article analyzes the theoretical foundations of individualization in higher education, its role in strengthening students’ professional knowledge, practical skills, reflective abilities, and creative potential. Special attention is paid to mechanisms such as diagnostic assessment of students’ educational needs, differentiated learning tasks, flexible pedagogical support, competency-based instruction, individual educational trajectories, mentoring, feedback, and the integration of modern educational technologies. The study emphasizes that the effective use of an individual approach contributes to the formation of professionally competent, socially active, and self-developing graduates. It is argued that improving professional training requires a systematic connection between theoretical knowledge, practical experience, personal motivation, and the requirements of future professional activity.